Enhancing healthcare access during disasters and emergencies: Recommendations from Nepali migrants in Japan - Sushila Paudel; Sakiko Kanbara (Elsevier, 2023)
Migrants in Japan often face difficulties accessing healthcare due to language barriers, lack of information, shortage of interpreters, amongst other barriers. With an increase in the number of foreigners in Japan, it is also expected that health and safety concerns for migrants will rise during times of crisis or disaster. The purpose of this article is to present recommendations from Nepali migrants themselves about various actions that stakeholders or policymakers could take to improve healthcare access during future disasters, emergencies, or crises in Japan. Recommendations from Nepali migrants in this study include mobilization of Nepali healthcare professionals, self-preparedness, a disaster information centre by the embassy, Nepali hotline services, telehealth services, and mutual help. By working together and leveraging available resources, it is possible to ensure that migrants are not left behind in the face of disasters and emergencies. Further research is required to determine the most effective ways to improve healthcare access for migrants in Japan during disasters, crises, or emergencies.